The association between personality traits and transphobia among university students: a cross-sectional study in northwestern Iran - Ali Reza Shafiee-Kandjani; Behzad Shalchi; Asal Raeisnia; Sara Tajlil; Elham Davtalab-Esmaeili (BMC Psychiatry)
Abstract Background Individuals with GD may suffer from limited access to healthcare services because of negative attitudes from the healthcare providers. Therefore, to promote medical service it is of great importance to address negative attitudes among healthcare providers. The present study aimed to estimate the prevalence of transphobia as well as to assess the association between personality traits and transphobia among students of the University of Medical Sciences, who will hold key positions within the healthcare system. Methods This cross-sectional study was conducted on 418 students at Tabriz in northwestern Iran in 2024. Convenience sampling method was utilized. Data were gathered through standard self-reported questioners; Genderism and Transphobia Scale (GTS), and Big Five Inventory scale (BFI-44). Linear regression analysis was conducted to estimate standard coefficient with 95% Confidence Intervals (CIs). Results The response rate was calculated as 98.35% in which 204 (48.8%) out of the participants were female. The mean (SD) age was 23.73 (2.01) years. The adjusted multiple linear regression coefficients indicated that the agreeableness (β = 0.16, p = 0.001), neuroticism (β = 0.11, p = 0.02), and openness (β = -0.27, p = 0.001) were able to effectively explain the variance in transphobia scores. However, conscientiousness (β = 0.06, p = 0.18) and extroversion (β = 0.06, p = 0.05) did not significantly contribute to explaining the variance in transphobia scores. Conclusions Personality traits may significantly influence attitudes toward transgender individuals, suggesting that interventions designed to reduce transphobia should consider these foundational personality characteristics. Clinical trial number Not applicable.